Impact of heteroatom (S and N) position and change in central ring of anthracene with heterocyclic ring on charge transport and optical properties in anthratetrathiazole (ATTz). (4th July 2019) - Tripathi, Anuj; Prabhakar, Chetti
ABSTRACT: Based on the results of quantum mechanical calculation extracted with the B3LYP functional at the density functional theory level, the impact of replacement of thiophene with thiazole rings in anthratetrathiophene (ATT) molecule was evaluated. Furthermore, to study the effect of substitution in the central benzene ring of anthracene, cyclic rings with heteroatoms were introduced. The optical and charge transport characteristics were also examined when the position of sulphur and nitrogen at the periphery of anthracene were interchanged. To analyze the electronic transitions in these molecules, TD-DFT calculations were performed. The outcome of the calculations suggest that swapping of the central benzene with hetero-cyclic rings and the change in positions of the sulphur and nitrogen have considerable influence on various properties, i.e. energies of HOMO & LUMO, HOMO-LUMO energy gap, ionization potential (IP), electron affinity (EA), hole extraction potential (HEP), electron extraction potential (EEP) and reorganization energies (λ). Moreover, all the studied molecules posed better hole and electron transport characteristics than standard materials. The smaller values of hole and electron reorganization energies suggest that this analysis offers a supportive background for prospective design and fabrication of high-performance charge-transport materials. Highlights On interchanging position of S and N at the periphery of ATTz results, a small change in absorption maxima. Replacement of central six-member ring of anthracene with a five-member ring in ATTz molecule results in blue-shifted absorption. Molecules where sulphur facing outward at the periphery of ATTz are better for hole transporting materials. On changing the position of S-atom (inward to outward position) at the periphery of ATTz lead to destabilization of both HOMO and LUMO levels. GRAPHICAL ABSTRACT: